SLOPE DESIGN OF DUMPING AREA IN PT BHUMI RANTAU ENERGI, SOUTH BORNEO - AGUSTIAN (NIM : 12109012), KRISTIJULIANTIKA
PT Bhumi Rantau Energi (PT BRE) is located in Rantau, South Borneo. On June 2013, west side of disposal area is failure and followed by the east side on July 2013. In the future, this failure area is still needed as disposal area. Therefore geotechnical analysis must be conducted to understand the cause of failure and to give recommendation for the next dumping activity. Geotechnical analysis with limit equilibrium method will be carried out using Slide 6.0 software from Rocscience. Data for this research is taken from geotechnical test based on residual shear strength. Samples from disposal area are used as supporting data. The cause of failure is predicted due to deterioration of material qualities. From the result of analysis, disposal volume addition can be carried out but the next dumping activity must be done layer by layer and compacted. For the west dump slope, it is recommended to use 65 meter overall slope with 11o slope angle while for the east dump slope, it is recommended to use 60 meter overall slope with 10o slope angle.